2021
DOI: 10.3892/mmr.2021.12536
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback loop of lncRNA FAM201A/miR‑146a‑5p/POU2F1 regulates IL‑1β‑induced chondrocyte injury in vitro

Abstract: Numerous studies have previously demonstrated that long non-coding RNAs (lncRNAs) serve an important regulatory role in osteoarthritis (OA). In particular, the lncRNA family with sequence similarity 201 member A (FAM201A) was previously found to be downregulated in necrotic femoral head samples. However, the role of FAM201A in IL-1β-induced chondrocyte injury remains unclear. It was hypothesized that FAM201A may exert a protective effect on IL-1β-induced chondrocyte injury in OA by sponging microRNAs (miRNAs/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…High-throughput sequencing revealed that POU2F1 is a target gene of microRNA-205-5p (miR-205-5p) and miR-146a-5p. 32 , 33 Another study revealed that the expressions of miR-205-5p and miR-146a-5p were increased by physical training. 34 Wang et al 35 found that exercise training could decrease the level of long noncoding RNA taurine upregulated gene 1.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing revealed that POU2F1 is a target gene of microRNA-205-5p (miR-205-5p) and miR-146a-5p. 32 , 33 Another study revealed that the expressions of miR-205-5p and miR-146a-5p were increased by physical training. 34 Wang et al 35 found that exercise training could decrease the level of long noncoding RNA taurine upregulated gene 1.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA plays an important regulatory role in disease by interacting with disease‐associated microRNA and have also been shown to mediate chondrocyte apoptosis 72 . Due to the close relationships and similar effects among the above three, we list them as regulating chondrocyte apoptosis in Table 1 instead of showing them one by one 73–97 …”
Section: Apoptosismentioning
confidence: 99%